Rethinking the measures of poverty - Seppo Sallila; Heikki Hiilamo; Reijo Sund (Luxembourg Income Study (LIS), 2004)
This study attempts to introduce a new method to measure relative income poverty. The aim is to find a solution which will combine information both on the depth of poverty and the quantity of the poor, i.e. the number of people living in poverty. Furthermore, a yardstick is sought which would be relatively simple and easy to understand, as these properties would facilitate the use of the new method in sociological poverty research and political decision making. The paper begins by discussing the most common problems in measuring social exclusion and relative income poverty. The following sections focus on poverty alleviation policies and poverty measurement practices, as well as on different poverty indices and the properties of an ideal poverty measure. Next, our innovation is presented, the cumulative poverty index (CUPI), together with a section discussing the estimations of the new index. The properties of the CUPI are analysed by comparing it to a number of commonly used poverty and inequality measures. Before introducing conclusions, poverty trends are compared and simulations calculated to test the CUPI against the most common relative income poverty measures.
Keywords: 330; Armut; Armutsbekämpfung; Messung; Sozialer Indikator; Finnland